Properties of wood-based composites manufactured from densified beech wood in viscoelastic and plastic region of the force-deflection diagram (FDD) - Sikora Adam (De Gruyter, 2021)
It is still little or no knowledge about the properties of layered wood-based composites and nonwood components in the viscoelastic and plastic region of the force-deflection diagram (FDD). The properties of composites in this area are influenced by several factors such as the composition of the layered composite, the method of modification of the individual layers, the type of adhesive used, etc. This paper focuses on the analysis of the effect of the thickness of individual layers (5 and 9 mm) of beech wood (Fagus sylvatica L.), modification of these layers with different degrees of densification (10, 20, 30, and 40%) and the type of the nonwood component (carbon and high-strength glass fibers) used to reinforce the layered composite on the properties of materials in the plastic region of the FDD. The paper describes the impact of selected factors and those interactions behavior of the tangent modulus in the whole FDD. This is the first study that describes the development of layered wood-based composites and nonwood components in the viscoelastic and plastic region and analyzes the impact of most imported types of modifications on the characteristics in the viscoelastic and plastic regions.